Temperature-dependent Raman spectroscopy and sensor applications of PtSe2 nanosheets synthesized by wet chemistry - Pawar, Mahendra S.; Late, Dattatray J. (Beilstein Journal of Nanotechnology, 2019)
We report on a wet chemistry method used to grow PtSe2 nanosheets followed by thermal annealing. The SEM and TEM analysis confirms the formation of PtSe2 nanosheets. Furthermore, XRD, Raman, XPS and SAED patterns were used to analyze the crystal structure and to confirm the formation of the PtSe2 phase. The temperature-dependent Raman spectroscopy investigations were carried out on PtSe2 nanosheets deposited on Si substrates in the temperature range 100-506 K. The shifts in Raman active E-g and A(1g) modes as a function of temperature were monitored. The temperature coefficient for both modes was calculated and was found to match well with the reported 2D transition metal dichalcogenides. A PtSe2 nanosheet-based sensor device was tested for its applicability as a humidity sensor and photodetector. The humidity sensor based on PtSe2 nanosheets showed an excellent recovery time of approximate to 5 s, indicating the great potential of PtSe2 for future sensor devices.
Keywords: nanosheets; PtSe2; Raman spectroscopy; Sensor; thermal effect